Предмет: Математика,
автор: california3
производная от 1+cosx1-cosx
Ответы
Автор ответа:
0
u=1+cosx v=1-cos (u/v) ' = (1/v²)(u' v- v ' u) =
= (1/(1-cosx)²)(-sinx(1-cosx)-sinx(1+cosx)=1/(1-cosx)²(-sinx+sinxcosx-sinx-sinxcosx)=-2sinx/(1-cosx)²
= (1/(1-cosx)²)(-sinx(1-cosx)-sinx(1+cosx)=1/(1-cosx)²(-sinx+sinxcosx-sinx-sinxcosx)=-2sinx/(1-cosx)²
Похожие вопросы
Предмет: Математика,
автор: valerialutyh
Предмет: Українська мова,
автор: Аноним
Предмет: Английский язык,
автор: 232004
Предмет: Литература,
автор: ruslannasibov